The Impact of Renal Denervation on the Progression of Heart Failure in a Canine Model Induced by Right Ventricular Rapid Pacing - Chen, Wei-Jie; Liu, Hang; Wang, Zi-Hao; Liu, Chang; Fan, Jin-Qi; Wang, Zheng-Long; Xu, Yan-Ping; Zhang, Bo; Gyawali, Laxman; Li, Qiang; Ling, Zhi-Yu; Yin, Yue-Hui (Frontiers in Physiology, 2020)
Heart failure (HF) has been proposed as a potential indication of renal denervation (RDN). However, the mechanisms enabling RDN to attenuate HF are not well understood, especially the central effects of RDN. The aim of this study was to decipher the mode of operation of RDN in the treatment of HF using a canine model of right ventricular rapid pacing-induced heart failure. Accordingly, 24 Chinese Kunming dogs were randomly grouped to receive sham procedure (Sham-operated group), bilateral RDN (RDN group), rapid pacing to induce HF (HF-control group), and bilateral RDN plus rapid pacing (RDN+HF group). Echocardiography, plasma brain natriuretic peptide (BNP), and norepinephrine (NE) concentrations of randomised dogs were measured at baseline and four weeks after interventions, followed by histological and molecular analyses. Twenty dogs completed the research successfully and were enrolled for data analyses. Results showed that the average optical density of renal efferent and afferent nerves were significantly lower in RDN and RDN+HF groups than those in the Sham-operated group, with a significant reduction of renal NE concentration. Comparing with the Sham-operated group, rapid pacing in RDN+HF and HF-control groups induced a significant increase in left ventricular end-diastolic volume and decrease in left ventricular ejection fraction, and correspondingly resulted in cardiac fibrosis and dysfunction. Cardiac fibrosis evaluated by Masson’s trichrome staining and the expression of transforming growth factor-β1 (TGF-β1) were significantly higher in HF-control group than those in Sham-operated group, which were remarkably attenuated by the application of RDN technique in the RDN+HF group. In terms of central RAS, comparing with that in Sham-operated group, the expression of AngII/ACE/AT1R in the hypothalamus of dogs in HF-control group was upregulated, and that of the Ang (1-7)/ACE2 was downregulated. Furthermore, both of them were significantly attenuated by the RDN therapy in the RDN+HF group. In conclusion, RDN technique could damage renal nerves and suppress the cardiac remodelling procedure in HF canines while concomitantly attenuating the overactivity of central RAS in the hypothalamus.